DOES INTELLECTUAL CAPITAL STRENGTHEN ENVIRONMENTAL DISCLOSURE ON FINANCIAL PERFORMANCE DURING COVID-19? - Evi Marlina, Maria Asumpta; Swastidevi, Luisa Amira; Dwi Radianto, Wirawan Endro (Faculty of Economics and Business University of Mataram, 2024)
This research aims to examine the moderating role of Intellectual Capital (IC) on the influence of Environmental Disclosure (ED) on Financial Performance (FP) in the energy sector listed on the IDX for the period 2020 to 2022. The analysis uses Ordinary Least Square (OLS). The research results found that IC was able to moderate the relationship between ED and EP. This research contributes to the RBV theory regarding IC, an intangible asset in this case that can play a role in increasing ED and FP and encouraging the company's competitive advantage. Apart from that, this research also contributes to sustainability theory, which states that sustainability in companies requires the role of IC as a variable that can encourage ED to increase FP. Thus, IC becomes an important variable that companies must consider to increase FP while still paying attention to sustainability factors.